BJOG Editor's Choice. (January 2016) - Chien, Patrick
Abstract : Deputy Editor‐in‐Chief, Dr Patrick Chien, discusses his top articles from this issue in an audio podcast available athttps://soundcloud.com/bjog/january-editors-choice-2016 Abstract : Deputy Editor‐in‐Chief, Dr Patrick Chien, discusses his top articles from this issue in an audio podcast available athttps://soundcloud.com/bjog/january-editors-choice-2016